FACTORS AFFECTING QUALITY IMPROVEMENT OF LIFE IN PATIENTS WITH POST-TRANSFEMORAL AMPUTATION - NUR RACHMAT; MOHAMMAD FANANI; DARSONO DARSONO; SUWARTO SUWARTO (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The study aims to investigate the contributions of self-efficacy, motivation, religiosity, social support, optimism, and subjective well-being as factors affecting quality of life on individuals with transfermoral amputation. Through empowerment, it is expected that there will be an increase in independence and socioeconomy. The ultimate goal of the empowerment process is for independence. Methods: This study used observational analytic with cross-sectional approach. The sample in this study was 110 post-transfemoral amputation patients. Data taken from questionnaires of self-efficacy, motivation, religiosity, social support, optimism, subjective well-being and quality of life were analyzed using structural equation modeling. Results: There was no influence of motivation on quality of life (critical ratio [CR]=0.535 <1.96; p=0.592 <0.05). There was a statistically significant positive effect of self-efficacy on quality of life (CR=3.082> 1.96; p=0.002 <0.05). There was a statistically significant positive effect of religiosity on quality of life (CR=2.919> 1.96; p=0.004 <0.05). There was no influence from social support for quality of life (CR=0.082 <1.96; p=0.935 <0.05). There was a statistically significant positive effect of optimism on quality of life (CR=2.307> 1.96; p=0.021 <0.05). There was a statistically significant positive effect of subjective well-being on quality of life (CR=2.089> 1.96; p=0.037 <0.05). Conclusion: The quality of life of patients with post-transfemoral amputation is positively and significantly influenced by optimism, religiosity, self-efficacy, and subjective well-being.